The Use of Microarray Technology for the Analysis of Streptococcus Pneumoniae. Issue 4 (2002) - McCluskey, Jackie; Dowson, Christopher G.; Mitchell, Timothy J.
Abstract : Streptococcus pneumoniae is an important human pathogen associated with pneumonia, septicaemia, meningitis and otitis media. It is estimated to result in over 3 million child deaths worldwide every year and an even greater number of deaths among the elderly. Prior to the complete sequencing of the genomes of S. pneumoniae TIGR4 (serotype 4) and S. pneumoniae R6 (serotype 2), we designed a custom miniarray consisting of 497 pneumococcal genes. The overall objectives of our microarray investigations were, first, to assess the genetic diversity between different S. pneumoniae serotypes, clinical isolates and also different Streptococcus species; second, we aimed to use microarray technology to examine the mechanisms by which environmental factors influence pneumococcal gene expression, and ultimately to further the understanding of how these changes in gene expression are achieved and how they may alter the virulence of the organism.